Analysis of the Effect of Product Quality and Promotion on Yarn Purchase Interest at PT. Hoja Indonesia - Zafa, M. Rudi; Edison; Yesi, Reni (Mulia Pratama, 2024)
Product quality and promotion are important supporting factors to increase purchasing interest. This is because good product quality and promortion will be able to increase sales, so that the company makes a profit and experiences development. Apart from that, the development and progress of the company from customers who make purchase continuously. The aim of this research is to determine the effect of product quality and promotion on interest in buying yarn. This research was conducted at PT. Hoja Indonesia. This research time, in collecting data, was from November 2023 to February 2024. The research methods used were classical assumption test analysis, multiple linear regression analysis and goodness of fit teast, using Eviews. Based on the results of multiple linear regression analysis, it was obtained that Y = 4,1648 + 0,4635 X1 + 0,4412 X2 it explained that if product quality and promotion are not improved or the value is 0 (zero), then interest variabel will increase by 0,4635, assuming the order independent variables remain constant. If the promotion is increased by 1 unit, the purchase interest variable will increase by 0,4412 assuming the other independent variables remain constant. Based on the results of the coefficient of determination (R2) or square, it was obtained at 0,789 or 78,9%. This shows that the ability of product quality (X1) and promotion (X2) variables to purchase interest (Y) can be explained by 0,7895 or 78,9% while the remainder (100%-78%) = 21,1% is influenced by other variables not studied. Based on the t-test for hypotestis one, it shows that product quality (X1) has a positive and sig. effect on purchasing interest (Y), with a positive coefficient value obtained t-count > t-table or 2,7610>1,684 with significance level of less that 0,05 which is 0,0089. The results of the second hypothesis t-test show that promotion (X2) has a positive and significant effect on interest in buying yarn (Y) at PT. Hoja Indonesia, with a positive coefficient value of t-count>t-table or 2,777>1,684 with a significance level of less than 0,05, namely 0,0086. Based on the results of the f-test for the third hypothesis, it shows that product quality (X1) and promotion (X2) together have a positive and significant effect on interest in buying yarn (Y) at PT. Hoja Indonesia, with f-count>f-table or 74,1692>3,232 with significace level of less that 0,005, namely 0,000.